2011
DOI: 10.1021/jp2094824
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Exploration of Mode of Binding of ctDNA with 3-Hydroxyflavone: A Contrast to the Mode of Binding with Flavonoids Having Additional Hydroxyl Groups

Abstract: Binding interaction of 3-hydroxyflavone (3HF), a bioactive flavonoid, with calf-thymus DNA (ctDNA) has been explored exploiting various experimental techniques. The dual fluorescence of 3HF resulting from the excited state intramolecular proton transfer (ESIPT) is modified remarkably upon binding with the biomacromolecule. The determined binding constant, fluorescence quenching experiment, circular dichroism (CD) study, comparative binding study with the known intercalative binder ethidium bromide and thermome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
115
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 50 publications
9
115
0
Order By: Relevance
“…To study the interaction of small molecules with DNA, T m of the DNA solution in the absence and presence of small molecules or drugs are recorded. Small molecules that bind to DNA via an intercalation mode lead to stabilisation of DNA and results in an increase in the T m of DNA by about 5-8°C [18]. However, groove binding molecules do not alter the melting temperature of DNA duplex to such an extent [19].…”
Section: Thermal Denaturation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the interaction of small molecules with DNA, T m of the DNA solution in the absence and presence of small molecules or drugs are recorded. Small molecules that bind to DNA via an intercalation mode lead to stabilisation of DNA and results in an increase in the T m of DNA by about 5-8°C [18]. However, groove binding molecules do not alter the melting temperature of DNA duplex to such an extent [19].…”
Section: Thermal Denaturation Studiesmentioning
confidence: 99%
“…3-Hydroxyflavone (3HF) is a groove binding molecule that does not increase the T m of DNA while Quercitin (Q) follows intercalating mode and increases T m significantly. Figure is reproduced with permission from the manuscript of Jana et al [18].…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…6 Furthermore, it was found to improve the therapeutic index of chemotherapy agent cisplatin around two-fold. 7 Procaine in a small dose of 2 mM has shown cytotoxicity to leukemic cells with further enhancement in the cytotoxicity at 42 C. 8 The most noticeable role of procaine related to the cancer chemotherapy is the demethylation of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some food additives such as dyes [16][17][18] and sweeteners [19,20] bound to DNA were also investigated. These studies are valuable for exploring the structural and functional features of the biomacromolecule to decipher its biophysical processes [21], and can provide useful information for further understanding the toxicology of the chemicals. Kashanian et al reported that BHA interacted with DNA via an intercalative mode [22].…”
Section: Introductionmentioning
confidence: 99%